Psychological therapy in prosthetic treatment - Listopad, Justyna; Szymańska, Jolanta (Current Problems of Psychiatry, 2012)
Prosthetic treatment aims at the restoration of the stomatognathic system normal function. An extremely important element of prosthetic rehabilitation is an appropriate psychological-pedagogical conduct of doctors towards patients, which is related to psychological problems on the part of patients. A successful psychological therapy is frequently decisive for a successful prosthetic treatment, especially in completely edentulous patients, a large percentage of whom are elderly people.